Adaptation to chronic benign pain in elderly adults (2015)
ABSTRACT: This study sought to comprehend and analyze the experience of living with chronic benign pain during aging from the perspective of the adaptation model by Callista Roy. Methodology. Ours was an exploratory descriptive study using for analysis tools from the theory based on criteria by Strauss and Corbin. The strategy involved in-depth interviews of 10 elderly adults residing in Medellín, Antioquia, and Chía, Cundinamarca (Colombia) with chronic benign pain. Results. In elderly adults, behaviors were identified that were secondary to the presence of pain and which are consequence of the capacity to adapt to their experience, managing to modify the environment by using internal and external resources that permitted their controlling the paingenerating stimuli in the human beings adaptation means based on the Adaptation model by Callista Roy. Conclusion. Elderly adults respond effectively to their new secondary condition:presence of benign pain in all the means of adaptation.